Spinosad application in an apple orchard affects both the abundance of the spider Araneus diadematus and its web construction behaviour - Mazzia, Christophe (Ecotoxicology (London, England), 2020)
The principles of organic production are based on the respect of ecological processes including the promotion of natural enemies to control pests. However, as a last resort, some natural pesticides can be applied such as the pesticide spinosad. This neurotoxic insecticide is now widely used even in non-organic production systems. As generalist predators, spiders, and especially orb web spiders, which prey on flying pests, are thought to be useful for biocontrol. To study the effects of spinosad on orb web spiders, we applied spinosad (Success4®) at the normal application rate (96 g ha-1) in an orchard covered by nets where Araneus diadematus was very abundant. Its abundance (number of webs), location when present on the web and web characteristics were determined one day before (D - 1) and 1, 3, 6, 10 and 14 days after the application (D + 1, D + 3, D + 6, D + 10 and D + 14). After spinosad application, at D + 1 and D + 14, the number of A. diadematus webs decreased by 28% and 47%, respectively, compared to D - 1 where we observed on average 0.2 webs m-2. This decrease is likely due to a combination of direct pesticide effects, reduced prey availability and mechanical effects of the air blast sprayer. The short-term toxicity of spinosad was assessed using behavioural markers: (i) the percentage of abnormally located spiders (i.e. neither in the centre of the web nor hidden under the apple leaves) for 30 and 50% of the webs at D + 1 and D + 3 respectively, (ii) the percentage of incomplete webs (made only of the non-sticky spiral) in 35 and 75% of the cases at D + 1 and D + 3 respectively and (iii) one web characteristic, the mean parallelism between spirals, that was significantly reduced at D + 1 compared to D - 1. The study of the other web characteristics indicated that spiders did not modify the capture area but rather significantly decreased their investment in silk at D + 6 and D + 10 by reducing the number of radii and spiral turns. Overall, the application of spinosad (Success4®), representing a triple disturbance (mechanical, toxicological and alimentary), has a negative impact on the orb web spider A. diadematus and should thus be used with caution if growers want to promote the contribution of these spiders to natural biocontrol in their fields